2008
DOI: 10.1108/17537980810890284
|View full text |Cite
|
Sign up to set email alerts
|

Cohesiveness within teamwork: the relationship to performance effectiveness – case study

Abstract: Purpose -This paper aims to explore the nature and the function of teamwork cohesiveness in organizations in the UAE. Design/methodology/approach -While many organizations are successful at managing the materials and machinery of the organization, they fall short in managing the human side of their business. This research addresses and assesses how teams can progress to be of maximum use through teamwork and to view teams as performing organizational units which is similar to other studies that focus on teamwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…That aspect of the process has a stronger effect on commitment for teams involved in more complex knowledge work rather than less complex work. (Al-Rawi, 2008) also concluded that team cohesiveness had an effect on commitment. (Weick et al, 1999) found cohesiveness had an impact on commitment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…That aspect of the process has a stronger effect on commitment for teams involved in more complex knowledge work rather than less complex work. (Al-Rawi, 2008) also concluded that team cohesiveness had an effect on commitment. (Weick et al, 1999) found cohesiveness had an impact on commitment.…”
Section: Discussionmentioning
confidence: 98%
“…The results of his research include showing that the manager's integrity behavior influences commitment. (Al-Rawi, 2008), as seen in his research entitled "Cohesiveness within Teamwork: the Relationship to Performance Effectiveness: Case Study". His research was conducted on government employees in Abu Dhabi with a sample of 294 people.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
“…trying to form the best group (KT1), communicate dynamically (KT2), and routinely coordinate (KT3). Teamwork was measured using three items from questions developed by Al-Rawi (2008), Ivancevich et al (2005), Hoegl and Gemuenden (2001).…”
Section: Measurements Of Teamwork Indicatorsmentioning
confidence: 99%
“…trying to be loyal to the department (KA1), proud of the department (KA2), trying to become part of the department/ study program (KA3), and has a suitability value (KA4). Measurement of affective commitment variable uses the four-item questions from Allen and Meyer (1993), Al-Rawi (2008), and Mayhew, Ashkanasy, Bramble, and Gardner (2007).…”
Section: Measurement Of Affective Commitment Indicatorsmentioning
confidence: 99%
“…However, in the current study, students who maintain a cordial relationship with other team members, and who gets going with the other team members to fulfil their part according to the terms and conditions agreed upon, are the ones who is satisfied with the teamwork. Hence, we can say that team cohesiveness is required for effective functioning of teams in educational institutions(Al-Rawi, 2008). Every student has a limitation on the amount of workload he/she can handle before things become out of control.…”
mentioning
confidence: 99%